2010
DOI: 10.1071/rd09302
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of endometrial gene expression and metabolic parameters in beef heifers yielding viable or non-viable embryos on Day 7 after insemination

Abstract: Abridged title: Endometrial gene expression and metabolic parameters in subfertile beef heifers. AbstractThe objective of this study was to compare the hormonal, metabolic characteristics and endometrial gene expression profiles in beef heifers yielding either a viable or a degenerate embryo on Day 7 after insemination as a means to explain differences in embryo survival.Oestrus was synchronised in cross bred beef heifers (n=145) using a CIDR-prostaglandin protocol and heifers (n=102) detected in standing oest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 68 publications
4
42
0
Order By: Relevance
“…The limited role of AGPAT4 was observed in endometrial tissues obtained from beef heifers showing its role in embryo survival. The rate of embryo survival correlated well with the abundant expression of AGPAT4 [25].…”
Section: Human Agpat3 and Agpat4mentioning
confidence: 75%
“…The limited role of AGPAT4 was observed in endometrial tissues obtained from beef heifers showing its role in embryo survival. The rate of embryo survival correlated well with the abundant expression of AGPAT4 [25].…”
Section: Human Agpat3 and Agpat4mentioning
confidence: 75%
“…[37]), endometrium related to embryo survival ( DGKA, BSP3, etc. [26]), endometrium in lactating cows compared to non-lactating cows ( APBB1, ST13, etc. [38]) or pregnant cows compared to non-pregnant cows ( ASL, GPLD1, etc.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed genes whose expression in tissues or cells of importance to reproduction vary with reproductive status; these genes are candidates for containing SNPs that impact fertility. For example, genes were identified that were differentially regulated in the brain of cows displaying strong estrus compared to those displaying weak estrus [25], in the endometrium of heifers which produced viable embryos compared to those which produced non-viable embryos [26], and in biopsies from embryos that resulted in live calves as compared to embryos that died following embryo transfer [27]. Genetic variants in the genes differentially expressed in the aforementioned studies and others may be responsible for differences in fertility among animals.…”
Section: Introductionmentioning
confidence: 99%
“…In order to characterise possible mechanisms leading to the up-or down-74 regulation of the initially identified genes, a further 8 genes were chosen in order to further 75 identify these. 76 Beltman et al (2010). 78…”
Section: Quantitative Real-time Pcr (Q-rt-pcr) 71mentioning
confidence: 99%
“…In a previous study (Beltman et al, 2010) The experimental design used for this study was as previously described (Beltman et al, 58 2010). Oestrus was synchronised in cross-bred beef heifers (n=157) using a Controlled 59…”
Section: Introduction 31mentioning
confidence: 99%